PVA-Assisted Sol-Gel Synthesis and Structural Characterisation of CuO-Coated LiMnPO4 Olivines - K. Rajammal; D. Sivakumar; M. Z. Selamat; R. Nadlene; C.K. Kok (International Journal of Integrated Engineering, 2026)
This study examines the influence of different weight percentages of CuO coating (1, 2, and 3 wt.%) on the structural properties of LiMnPO4 cathode materials synthesised by the polyvinyl alcohol (PVA)-assisted sol–gel method. PVA acted as a carbon source during synthesis, producing an in situ carbon layer that improves the conductivity of the composite. XRD analysis confirmed the formation of a pure olivine LiMnPO₄ phase without impurity peaks, indicating that the CuO coating did not alter the main structure. SEM and EDAX analyses verified the uniform distribution of the CuO layer and the presence of carbon. The 2 wt.% CuO-coated sample showed the smallest crystallite size (33.8 nm) and the lowest strain value (1.28 × 10-3), compared to the pristine LiMnPO₄ (86.6 nm, 2.43 × 10-3). These results suggest that the optimised CuO coating helps control particle growth and enhances structural uniformity, which could contribute to better electrochemical stability in future applications.